2022
DOI: 10.3390/w14111696
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress Thresholds and Evaluation of Coefficient Ks for Perennial Ryegrass in Tropical Conditions

Abstract: Perennial ryegrass (Lolium perenne) is the predominant forage crop in the equatorial highland zones of Colombia due to its high nutritional value and versatility to produce both milk and meat. This study aimed to determine the relationship between the relative depletion of usable soil water and the Ks values of canopy expansion and closure stomatal of perennial ryegrass, as well as to identify the threshold values of water stress. The experiment was carried out in pots under a controlled environment condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Water deficit reduced root length. These results were consistent with those of other researchers on Quercus leucotrichophora [70], Thymus volgaris [44], and Tritipyrum lines [71]. Previous researchers have reported that root cell final lengths are smaller under water deficit [72] due to a decrease in root apical cell elongation under water stress [58].…”
Section: Discussionsupporting
confidence: 93%
“…Water deficit reduced root length. These results were consistent with those of other researchers on Quercus leucotrichophora [70], Thymus volgaris [44], and Tritipyrum lines [71]. Previous researchers have reported that root cell final lengths are smaller under water deficit [72] due to a decrease in root apical cell elongation under water stress [58].…”
Section: Discussionsupporting
confidence: 93%
“…They include canopy cover (CC), canopy growth coefficient (CGC), canopy decline coefficient (CDC), crop coefficient for transpiration at full CC, and normalized water productivity (WP*) for biomass formation. Crop water stress parameters (soil water depletion thresholds for leaf growth inhibition and stomatal conductance and for acceleration of canopy senescence) were taken from Terán-Chaves et al [41]. The crop parameters were iteratively adjusted with the help of the Independent Parameter Estimation Model (PEST) Ver.…”
Section: Crop Datamentioning
confidence: 99%
“…K cb values from this technique were used to estimate the reduction of transpiration as the water stress term K s (Trout and DeJonge, 2021). Formulations to calculate K s include a linear reduction in transpiration as deficit exceeds the Readily Available Water (RAW) as suggested by FAO-56 (Allen et al, 1998), but more recently an exponential decay function was used, e.g., as defined by Aq-uaCrop (Steduto et al, 2009) and reinforced by other studies (Trout and DeJonge, 2021;Terán-Chaves et al, 2022).…”
mentioning
confidence: 99%